The Chinese debate about Soviet socialism, 1978-1985 - Rozman, Gilbert (Princeton legacy library., 1987)
This study, based largely on Chinese journals rarely available to Western scholars, explores the abrupt turnabout of Chinese views of the Soviet Union from condemnations of revisionism" to appreciation for problems common to both countries. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905